Risk Factors, Characteristics, and Outcome in Non-Ventilated Patients with Spontaneous Pneumothorax or Pneumomediastinum Associated with SARS-CoV-2 Infection - Marza AM; Petrica A; Lungeanu D; Sutoi D; Mocanu A; Petrache I; Mederle OA (International Journal of General Medicine, 2022)
Adina Maria Marza,1,2 Alina Petrica,1,3 Diana Lungeanu,4 Dumitru Sutoi,1,5 Alexandra Mocanu,6 Ioan Petrache,1,7 Ovidiu Alexandru Mederle1,2 1Department of Surgery, “Victor Babes” University of Medicine and Pharmacy, Timisoara, 300041, Romania; 2Emergency Department, Emergency Clinical Municipal Hospital, Timisoara, 300079, Romania; 3Emergency Department, “Pius Brinzeu” Emergency Clinical County Hospital, Timisoara, 300736, Romania; 4Center for Modeling Biological Systems and Data Analysis, Department of Functional Sciences, “Victor Babes” University of Medicine and Pharmacy, Timisoara, 300041, Romania; 5Clinic of Anaesthesia and Intensive Care, “Pius Brinzeu” Emergency Clinical County Hospital, Timisoara, 300736, Romania; 6Department of Infectious Diseases, “Victor Babes” University of Medicine and Pharmacy, Timisoara, 300041, Romania; 7Clinic of Thoracic Surgery, Emergency Clinical Municipal Hospital, Timisoara, 300079, RomaniaCorrespondence: Alina PetricaDepartment of Surgery, “Victor Babes” University of Medicine and Pharmacy, Piata Eftimie Murgu 2, Timisoara, 300041, RomaniaTel +40744772427Email alina.petrica@urgentatm.roDiana LungeanuCenter for Modeling Biological Systems and Data Analysis, Department of Functional Sciences, “Victor Babes” University of Medicine and Pharmacy, Piata Eftimie Murgu 2, Timisoara, 300041, RomaniaEmail dlungeanu@umft.roBackground and Objectives: Spontaneous pneumothorax (SP) and spontaneous pneumomediastinum (SPM) have frequently been cited as complications associated with coronavirus disease 2019 (COVID-19) pneumonia, with especially poor prognosis in mechanically ventilated patients. The current literature is controversial regarding the potential risk factors for developing SP or SPM (SP-SPM) in non-ventilated COVID-19 patients. Our research addressed a twofold objective: (a) to investigate the characteristics of patients with SP-SPM (both with and without COVID-19) and compare them to patients with sole COVID-19; (b) to quantify the risk of in-hospital mortality associated with SP-SPM and COVID-19.Patients and Methods: A retrospective case–control study was conducted in the emergency departments (ED) of two tertiary hospitals in Timisoara, Romania, over one year (1st April 2020‒31st March 2021; 64,845 records in total) and 70 cases of SP-SPM were identified (both SARS-CoV-2 positives and negatives). The control group comprised COVID-19 patients with no SP-SPM, included at a 2:1 ratio. Logistic regression was employed to quantify the in-hospital mortality risk associated with age, SP-SPM, and COVID-19.Results: SP-SPM and COVID-19 were connected with prolonged hospitalization, a higher percentage of intensive care admission, and a higher mortality. SP-SPM increased the odds of death by almost four times in patients of the same age, gender, smoking status, and SARS-CoV-2 infection: OR = 3.758, 95% CI (1.443– 9.792). Each additional year of age added 9.4% to the mortality risk: OR = 1.094, 95% CI (1.054– 1.135).Conclusion: ED physicians should acknowledge these potential risks when attending COVID-19 patients with SP-SPM.Keywords: case–control study, in-hospital mortality, chest pain, dyspnea, chest CT, COVID-19